Body mass index and risk of knee osteoarthritis: systematic review and meta-analysis of prospective studies - Huaqing Zheng; Changhong Chen (BMJ Open)
Objectives Obesity is suggested to be a risk factor for knee osteoarthritis (OA). This meta-analysis aimed to examine the relationship between body mass index (BMI) and the risk of knee OA in published prospective studies.Design Meta-analysis.Studies reviewed An extensive literature review was performed, and relevant studies published in English were retrieved from the computerised databases MEDLINE, EMBASE and Cochrane.Methods The effect estimate (RR or HR) and its 95% CI are investigated on the basis of the evaluation of differences of knee OR risk in overweight or obesity versus those with normal weight. Category-specific risk estimates were further transformed into estimates of the RR in terms of per increase of 5 in BMI by using the generalised least-squares method for trend estimation. Studies were independently reviewed by two investigators. Subgroup analysis was performed. Heterogeneity and publication bias were assessed. Data from eligible studies were extracted, and the meta-analysis was performed by using the STATA software V.12.0.Results 14 studies were finally included in the analysis. The results showed that overweight and obesity were significantly associated with higher knee OA risks of 2.45 (95% CI 1.88 to 3.20, p<0.001) and 4.55 (95% CI 2.90 to 7.13, p<0.001), respectively. The risk of knee OA increases by 35% (95% CI 1.18 to 1.53, p<0.001) with a 5 kg/m2 increase in BMI. Subgroup analysis showed that obesity was an independent predictor of knee OA risk regardless of the study country, sample size, gender proportion of participants, duration of follow-up, presence of adjusted knee injury and assessed study quality above or below an NOS score of 8. No publication bias was detected.Conclusions Obesity was a robust risk factor for knee OA. Professionals should take a possible weight reduction into account for the treatment of knee OA whenever a patient is significantly overweight.